KONSUMSI AIR PUTIH DAN MINUMAN MANIS, SOFT DRINK/MINUMAN BERKARBONASI, MINUMAN BERENERGI, MIE INSTAN DAN MAKANAN OLAHAN PADA REMAJA - Novriani Tarigan (Jurnal Ilmiah PANNMED (Pharmacist, Analyst, Nurse, Nutrition, Midwivery, Environment, Dentist), 2023)
The increasing prevalence of non-communicable diseases from year to year is related to the consumption of food and drinks. Drinks are anything that can be consumed and can quench thirst, usually in liquid form. Instant noodles are types of food that contain high fat and sodium, while processed foods (meat, chicken, fish) are foods that contain a lot of harmful food additives. The purpose of this study was to describe the consumption of water, sweet drinks, soft drinks/carbonated drinks, energy drinks, instant noodles and processed foods (meat, chicken, fish). This type of research is descriptive research, the data is collected using a semi FFQ (Food Frequency Questionnaire) questionnaire. Data analysis was univariate, namely the percentage and average weight of adolescent food and beverage consumption, then categorized. The results of this study are more water consumption in the less category, sweet drinks, soft drinks/carbonated drinks, energy drinks, instant noodles and processed foods (meat, chicken, fish) are in the rare category.